Parallel And Series Electric Hybrid Vehicle Simulation - Tan, Han Peng (Universiti Sains Malaysia, 2018)
Today, conventional vehicle is the most common and popular vehicle type in the world. Due to the environmental issue, many kinds of vehicle had been developed and introduced as an alternative to replace conventional ICE vehicle. Hybrid electric vehicle, which combines the advantage of conventional ICE vehicle and electric vehicle is believe to be the most promising alternative vehicle structure to replace conventional ICE vehicle. In this paper, a simple mathematical model for the Perodua Myvi had been constructed and the fuel economy of the vehicle is simulated. The fuel economy of Myvi with 2 different architectures, series and parallel hybrid electric vehicle, are compared. The mathematical model is constructed to determine the feasibility of transforming a conventional Myvi to hybrid electric Myvi. The power management strategy for the vehicle are manipulated by a rule-based strategy to fulfil the condition of the drive cycle provided. The fuel economy of the Myvi is simulated by using backward-facing model based on the drive cycle. Simulation results are used to compare the performance for both architectures vehicle. The fuel economy for both type of architecture is compared with the conventional vehicle.